2009
DOI: 10.1074/jbc.m109.029439
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the RhoA Exchange Factor Net1 with Discs Large Homolog 1 Protects It from Proteasome-mediated Degradation and Potentiates Net1 Activity

Abstract: Net1 is a nuclear Rho guanine nucleotide exchange factor that is specific for the RhoA subfamily of small G proteins. Truncated forms of Net1 are transforming in NIH3T3 cells, and this activity requires cytoplasmic localization of Net1 as well as the presence of a COOH-terminal PDZ binding site. We have previously shown that Net1 interacts with PDZ domain-containing proteins within the Discs Large (Dlg) family and relocalizes them to the nucleus. In the present work, we demonstrate that Net1 binds directly to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 44 publications
1
36
0
6
Order By: Relevance
“…In chicken embryos, it was shown that downregulation of Net1, triggered by an unknown factor, shut down basal RhoA activity and drove the onset of EMT (Nakaya et al, 2008). In addition, Net1 has been involved in the regulation of adherens junctions through its interaction with the polarity protein Dlg1 Carr et al, 2009). This interaction was dependent on the formation of E-cadherin-mediated cell contacts whose disruption caused dissociation of Net1 from Dlg1, leading to Net1 degradation by the proteasome (Carr et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In chicken embryos, it was shown that downregulation of Net1, triggered by an unknown factor, shut down basal RhoA activity and drove the onset of EMT (Nakaya et al, 2008). In addition, Net1 has been involved in the regulation of adherens junctions through its interaction with the polarity protein Dlg1 Carr et al, 2009). This interaction was dependent on the formation of E-cadherin-mediated cell contacts whose disruption caused dissociation of Net1 from Dlg1, leading to Net1 degradation by the proteasome (Carr et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Net1 GEF has been implicated in the regulation of epithelial cell polarity and EMT (Nakaya et al, 2008;Carr et al, 2009). In chicken embryos, it was shown that downregulation of Net1, triggered by an unknown factor, shut down basal RhoA activity and drove the onset of EMT (Nakaya et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations